Application of Job Sequencing Policies in Refrigerated Truck Sequencing: A Case Study - Kasemset C. (2017)
© 2017 IEEE. First-come first-served (FCFS) is a general policy for refrigerated truck sequencing. However, adopting FCFS makes a company case study to face long waiting times before loading goods and inadequate parking areas for waiting trucks. To solve these problems, six dispatching rules are considered: latest departure time (LDT), smallest critical ratio (CR), shortest processing time (SPT), longest processing time (LPT), priority queueing considering density of customers (PQ-C), and priority queueing considering traffic congestion (PQ-T). Six-month historical data of trucks were collected and used for evaluating each rule. The minimum value of a truck's waiting time can be obtained when PQ-T has been tested. The results showed that using PQ-T can reduce 11.04% of the total waiting time when compare to FCFS. PQ-T is recommended for refrigerated truck sequencing mobile application development. This application can automatically generate the daily truck sequence.